Effects of Light Level and Nitrogen Supply on the Red Clover–Orobanche Minor Host–Parasite Interaction - Joel I. Jokinen; Louis J. Irving (Plants, 2019)
Infection by holoparasitic plants typically causes decreases in host mass, thought to be primarily as a result of resource abstraction. Inverse relationships have been noted between the number of Orobanche spp. parasites infecting a host and their mass, suggesting that the parasites compete for a shared resource pool, assumed to be recently fixed carbon (C). In clover, nitrogen (N) fixation requires a high proportion of daily photosynthate and represents a potential competitor for recently fixed C. We grew Trifolium pratense, either singly or parasitised by Orobanche minor, under high or low light levels, and with or without exogenous N supply. Low light and N deficiency led to decreased host biomass, while the damage caused by parasitism was proportionate to host mass. Parasitism caused reductions in host leaf mass, area, photosynthetic rates and shoot N concentration, but did not affect starch accumulation. Parasite mass as a proportion of system biomass was significantly higher when attached to plants grown at high light, which was attributed to higher photoassimilate supply, while the N supply had no effect. While both N limitation and parasitism caused reductions in host growth, little evidence of competition for C between N fixation and the parasites was noted.